Particle-reinforced metal matrix nanocomposites fabricated by selective laser melting : a state of the art review - Yu, Wen Hui (2020)
Significant progress has been made in understanding selective laser melting (SLM) process as well as fabrication of various materials using this technology. This paper covers the emerging research on particle reinforced metal matrix nanocomposites (MMNCs) with SLM and provides a comprehensive overview of the underlying scientific topics behind them. In order to provide a thorough basis for understanding and controlling of the SLM processing of MMNCs fabrication, the state of the art research from the perspective of materials and SLM processing parameters is reviewed. Feedstock preparation methods for MMNCs are emphasized and compared in detail. Mechanical properties of nanocomposites and the enhancing mechanisms due to reinforcement are discussed in depth, highlighting strength, microhardness and fatigue properties. Thereafter, defects, especially those associated with SLM processing, are also elucidated by discussing their classification, mechanisms of formation and tendency in MMNCs. Applications in aerospace, automobile, electronics and electronic packaging, and biomedical industry are illustrated. Summary of findings from this review and trends for future research in the development of MMNCs by SLM are addressed in the final section.